Herbivorous Reef Fish Interaction with the Habitat and Physicochemical Variables in Coral Ecosystems in the Mexican Tropical Pacific - Diana Morales-de-Anda; Amílcar Leví Cupul-Magaña; Consuelo María Aguilar-Betancourt; Gaspar González-Sansón; Fabián Alejandro Rodríguez-Zaragoza; Alma Paola Rodríguez-Troncoso (Oceans, 2024)
Herbivorous fish can mediate spatial competition between algae and corals, which is crucial for coral ecosystems. However, in areas with limited coral coverage like the Mexican tropical Pacific (MTP), this dynamic is not fully understood. This study, using a functional trait approach and ordination analysis, explores whether herbivorous reef fish assemblage influences the benthic habitat components or if physicochemical factors define the habitat variability in the MTP’s Cleofas and Marietas insular systems. We analyzed if this relationship persisted across systems and over time, and identified species traits tied to habitat variability. Island comparison analyses between Cleofas and Marietas reveal that both herbivorous reef fish and physicochemical variables shape the habitat. Cleofas had larger mobile herbivorous fish that formed groups related mostly to macroalgae cover. In contrast, temporal analysis of Marietas shows that the habitat is primarily shaped by physicochemical variables with herbivorous fish being mainly small farmer species related to branching corals. Notably, these closely situated insular systems present varied ecosystem mediators, influenced by diverse drivers including fish traits and environmental factors. This study underscores the potential of employing a framework of ecological species traits combined with ordination methods to unravel the distinct site dynamics that contribute to the persistence of coral ecosystems within the MTP.